IMPLEMENTASI DAN EVALUASI STANDAR OPERASIONAL PROSEDUR (SOP) UNTUK PENGAJUAN DAN PERSETUJUAN KREDIT DI PT. BPR BANK BANTUL (Perseroda) - Binawati, Enita; Kusumawati, Erin; Herinanto, Redy; Kurniawan, Taufan Adi; Pujisari, Yusti (LP2M STP Mataram, 2023)
This internship activity aims to find out: (1) Standard Operating Procedures (SOP) for submitting and approving credit (credit granting) at PT BPR Bank Bantul (Perseroda). (2) Implementation and evaluation of Standard Operating Procedures (SOP) for credit application and approval. (3) As well as knowing the obstacles faced and the solutions that were carried out in implementing credit applications and approvals at PT BPR Bank Bantul (Perseroda). The method of collecting data in solving is by interview method, observation method, and by way of documentation method. The results of the internship activities show that: (1) The credit granting procedures applied at PT BPR Bank Bantul are good and in accordance with the theory. (2) Standard Operating Procedures (SOP) for credit submission and approval at PT BPR Bank Bantul are in accordance with credit elements. (3) Obstacles in granting credit at PT BPR Bank Bantul include incomplete requirements from prospective debtors, lack of understanding regarding collateral applied by banks, so that many prospective debtors have their collateral rejected by the bank, as well as false information provided by prospective debtors . To overcome these obstacles, PT BPR Bank Bantul postponed credit disbursement and reviewed and conducted another survey to ensure that the data was correct